The Influence of Organizational Commitment, Organizational Culture, Leadership Style and Environment on Employee Performance in the Wood Processing Industry - Firdaus, Firdaus; Lusiana, Herlina (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
This study aimed to examine the effects of organizational commitment, organizational culture, leadership and working environment variables on employee performance in the small-scale woodworking industry in Alalak, Barito Kuala, South Kalimantan. Employee performance is a matter of concern because it affects the overall performance of the business. The study subjects included employees in the wood processing industry in Alalak area, Barito Kuala Regency, South Kalimantan. This study aimed to determine the influence of organizational commitment, organizational culture, leadership, and actual work environment on performance. The sampling technique used is proportional random sampling. Data analysis technique using multiple linear regressions. The results show that organizational commitment, organizational culture, leadership, and actual work environment have an impact on performance.